Teachers’ perceptions on the use of Information and Communication Technology for teaching Biology in Lesotho - Makuru, Bobojane (University of the Free State, 2020)
A plethora of benefits that information and communication technologies (ICTs) have for teaching and learning has long been proven. In the light of this, influence of teachers’ perceptions on their incorporation in teaching should not be disregarded. However, only a few empirical studies have focused on teachers’ perceptions on the integration of ICTs, and even fewer on such integration in a particular subject that is important to career choices such as biology. Therefore, this study aimed to examine, through the lens of technological pedagogical content knowledge (TPACK), the teachers’ perceptions on the use of ICTs in the teaching of biology in Lesotho secondary schools. The objectives were to investigate the ICT tools that teachers commonly use, describe the practices that characterise the patterns of use and determine the correlation between teachers’ perceptions and their use of ICTs for teaching. A descriptive, non-experimental survey variety of a quantitative research design, following a deductive strategy, was employed. A total of 107 respondents, selected by a systematic probability sampling technique, completed a questionnaire comprising close-ended items that were measured on a Likert scale. Data were analysed using the Statistical Package for Social Sciences (SPSS) program. The findings revealed that Lesotho secondary school biology teachers perceived themselves as being moderately competent in ICT applications and their incorporation into teaching-learning experiences. Also, it was found that teachers held positive perceptions on the educational use of ICTs. Nevertheless, they reported irregular use for teaching and most commonly used ICTs were found to be printers, the Internet, computers/laptops and projectors. Teachers’ irregular ICT practices were more inclined towards supporting their traditional teaching methods and improving their own knowledge. The commonest practices included lesson preparations, searching for information on the Internet, preparing handouts and assessing learners through tests. Furthermore, the results presented a weak, positive and generally statistically significant Spearman rank order correlation between teachers’ perceptions and their use of ICTs in teaching biology. The study recommended teacher development programmes to improve ICT competences and also necessary interventions by the relevant education authorities in terms of investment and policies.
Keywords: Dissertation (M.Ed. (Education Studies))--University of the Free State, 2020; Biology education; Science education; Information and Communication Technology; TPACK; Teachers’ perceptions; Curriculum implementation; Lesotho education; Technological pedagogical content knowledge (TPACK)